Developments of traditional value stream mapping to enhance personal and organisational system and methods competencies*. Issue 13 (3rd July 2017) - Sunk, Alexander; Kuhlang, Peter; Edtmayr, Thomas; Sihn, Wilfried
Abstract : This paper presents developments of traditional value stream mapping (VSM) related to enhancing system and method competencies of both individuals and organisations. Since systematic immersions in traditional VSM – a highly accepted technique for improving production systems – are necessary, this paper describes from a production research point of view approaches for systematic productivity increases, reduction of lead time and an approach to improve sustainability indicators of value streams. The introduced developments of VSM focus on the entire flow and on details, thus creating synergies for designing and improving value streams, processes and work systems both economically and ecologically. On the one hand, this paper shows how practical approaches respectively rationalisation concepts (Lean principles, VSM, Process Management, short-cyclic improvement routine, Methods-Time Measurement) are used in industry in order to manage and improve processes and value streams. On the other hand, sustainability management can be supported on shop floor with utilisation of VSM. It aims to extend the view on value streams of both researchers and practitioners in sense of system and methods competencies.